Emergent supply chains in the agrifood sector: insights from a whole chain approach. Issue 4 (8th June 2015) - Anastasiadis, Foivos; Poole, Nigel
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to report research into emergent supply chain management (SCM) practices in a context in which the imperative for business development requires efficient inter-firm collaboration. It explores the way key supply chain (SC) actors perceive entrepreneurial opportunities and evaluates their SC processes. Design/methodology/approach – A whole chain approach, using qualitative methods, was used to investigate retail, wholesale and production links, with a special focus on small businesses which predominate in the agrifood sector. The methodology used is of vital importance to understand the complexity of the sector and the interdependencies among stakeholders. Findings – Results suggest several SC malfunctions originating in diverse strategic planning practices and different entrepreneurial mentalities which hinder the process of emergence from traditional to more modern chain configurations. The fact that the nature of new opportunities in the agrifood sector (e.g. organics) was poorly understood, obstructs further development of the agrifood sector. Other key findings suggest problematic flows of information within the SC and minimal trust among stakeholders. Research limitations/implications – Sampling constraints suggest that caution should be exercised in extrapolating these conclusions elsewhere. Nonetheless, further investigation using similar approach should be applied in a wider context not only in Greece but also in other similar economies characterized by nascent SCs. Originality/value – The study investigates the entire SC of a vital sector for numerous small- and medium-sized enterprises, with lessons for diverse emerging agribusiness economies. Insights, not only for the direct SC stakeholders but also for policymakers, could serve to unlock the potential of such sectors and also the exploitation of new opportunities in emerging markets which can be stifled by stagnant sectoral structures and conservative business attitudes.